2009
DOI: 10.1208/s12249-009-9253-y
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan–Chondroitin Sulfate Based Matrix Tablets for Colon Specific Delivery of Indomethacin

Abstract: Abstract. The different approaches for targeting orally administered drugs to the colon include coating with pH-dependent polymers, design of time-release dosage forms, and the utilization of carriers that are degraded exclusively by colonic bacteria. The aim of the present study was to develop a single unit, sitespecific drug formulation allowing targeted drug release in the colon. Matrix tablets were prepared by wet granulation using cross-linked chitosan (ChI) and chondroitin sulfate (ChS) polysaccharides a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
27
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(32 citation statements)
references
References 24 publications
4
27
0
1
Order By: Relevance
“…The other combinations containing 5%, 10% and 20% of CS were similar to the control. In the upper spectral region, at 3000 cm -1 , there was a greater intensity of bands proportional to the addition of CS, which may be associated with the OH -group common to both CS and EFS (Evonik, 2015;Amrutkar, Gattani, 2009). When comparing the spectrum of the control film and spectra of films associated with CS, the non-appearance of new bands can be verified, except CS absorption bands.…”
Section: Ftirmentioning
confidence: 99%
See 1 more Smart Citation
“…The other combinations containing 5%, 10% and 20% of CS were similar to the control. In the upper spectral region, at 3000 cm -1 , there was a greater intensity of bands proportional to the addition of CS, which may be associated with the OH -group common to both CS and EFS (Evonik, 2015;Amrutkar, Gattani, 2009). When comparing the spectrum of the control film and spectra of films associated with CS, the non-appearance of new bands can be verified, except CS absorption bands.…”
Section: Ftirmentioning
confidence: 99%
“…In addition to this favorable characteristic, natural polymers are found in abundance, they have low toxicity, low cost and flexibility to chemical modification, making them suitable for use in pharmaceutical coatings (Amrutkar, Gattani, 2009). Chondroitin sulfate is a natural polymer studied as a carrier of drugs in the research and development of new therapeutic systems designed for controlled and site-specific delivery (Bunhak et al, 2015;Amrutkar, Gattani, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…From the FT-IR results, we concluded that -C-N-, -C=C-, N-H, C-N, N-O, O-H, C-Cl, C-Br, and C-H are the functional groups present in IR-PLGA NPs. Previously, FTIR analysis was also performed by other investigators to characterize this type of interactions between drugs and PLGA polymer [35][36][37].…”
Section: Ftirmentioning
confidence: 99%
“…Oral dosage forms delivering drug to colon are highly desirable to treat a variety of bowel diseases such as colon cancer, ulcerative colitis, and local inflammation (1). The target delivery offers the benefit of the direct treatment at the disease sites and fewer systematic side effects.…”
Section: Introductionmentioning
confidence: 99%